Targeting Poverty under Complementarities: Evidence from Indonesia's Unified Targeting System - Achmad Tohari; Christopher Parsons; Anu Rammohan (Institute of Labor Economics (IZA), 2017)
Combining nationally representative administrative and survey data with official proxy means testing models and coefficients, we evaluate Indonesia's three largest social programs. The setting for our evaluation is the launch of Indonesia's Unified Targeting system, an innovation developed to reduce targeting errors and increase program complementarities. Introducing a new method of evaluation under the condition of multiple programs, we show that households receiving all three programs are at least 30 percentage points better off than those receiving none. Importantly, the bias from failing to account for program complementarities is greater in magnitude than the benefits of receiving a single program.
Keywords: D04; I32; I38; O12; 330; poverty; targeting; Indonesia; complementarities